KETERPADUAN SISTEM JARINGAN ANTAR MODA TRANSPORTASI DI PULAU SULAWESI - M. Yamin Jinca (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2009)
The Sulawesi Island is a region which has been growing and the development related to the economicdevelopment - era and the global trade. The potency of natural resource and the geographic location ofSulawesi are very prospective to be promoted to the National and International Market. For the reason, theexistence of efficient and effective transportation network system can support the wheel of economy inSulawesi. The integrated infrastructure and service networks are therefor demanded to reduce travel time sothat transportation cost can also be minimized. This paper gives a description about the development ofinfrastructure network and the transportation service and how to develop integrated transportation networkthat makes transportation in Sulawesi will be more effective and efficient.Keywords: infrastructure, integrated transport, intermodes